Apostávamos no amor: gênero e a produção memorialística sobre a militância de mulheres contra a ditadura civil-militar brasileira (1976-2014) - Rocha, Raquel Caminha (2017)
This paper analyses the memorial production on and by women who participated in the resistance to a state of exception in Brazil known as Civil-Military Dictatorship (1964-1985). It analyses the transformations in the elaboration of memories made from that time until now, since they started being written during the dictatorship period, around the 1970’s, in books and are still in course nowadays in new media. Women participation on this process of elaboration of memories is indicated by gender marks since the discourse used during the reminding process is based on representations about the femininity and the masculinity with intention of having their demands fulfilled or, at least, heard. Within this process of elaboration of memories, we find out that the memories reaffirm the binary model of gender based on the traditional models of femininity and masculinity, even though, in their constructions, the differences between men and women are supposedly being questioned. Key-words: